2021
DOI: 10.1016/j.artd.2021.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Does Preoperative Opioid Consumption Increase the Risk of Chronic Postoperative Opioid Use After Total Joint Arthroplasty?

Abstract: Background: Risk-factor identification related to chronic opioid use after surgery may facilitate interventions mitigating postoperative opioid consumption. We evaluated the relationship between opioid use preceding total hip arthroplasty (THA) and total knee arthroplasty (TKA), and chronic use postoperatively, and the risk of chronic opioid use after total joint arthroplasty. Methods: All primary THAs and TKAs performed during a 6-month period were identified. Opioid prescription and utilization data (in oxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
2
8
1
Order By: Relevance
“…Despite the small proportion of patients with chronic episodes, the total number remains noticeable. Chronic opioid use after KR has also been documented in previous studies 37 39 53. Regarding opioid dosage, another Swiss study found lower maximum daily MED of non-cancer opioid applications compared with our calculated dosages 59.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Despite the small proportion of patients with chronic episodes, the total number remains noticeable. Chronic opioid use after KR has also been documented in previous studies 37 39 53. Regarding opioid dosage, another Swiss study found lower maximum daily MED of non-cancer opioid applications compared with our calculated dosages 59.…”
Section: Discussionsupporting
confidence: 82%
“…Another explanation may be a result of recommendations to detect and discontinue potentially inappropriate prescriptions specifically targeting this demographic population 78 79. Use of preoperative analgesics was a predictor of postoperative opioids, with preoperative opioid use being the strongest predictor, and is in line with numerous previous findings 9 37–44. Using analgesics might be associated with a higher prevalence of pain, increased pain sensitivity or opioid tolerance 80 81.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Preoperative At-Risk Patient Identification: Screening for Opioids Many investigators have focused on identifying risk factors for prolonged use of opioids after orthopaedic surgery [26][27][28] . Preoperative opioid consumption has been identified as a major risk factor of chronic opioid use after orthopaedic surgery [29][30][31][32][33] . Conditions such as chronic pain syndrome, back pain, fibromyalgia, chronic fatigue, and sleep disorders are also associated with prolonged use of opioids after surgery 34 .…”
Section: Effect Of Opioids On Orthopaedic Patientsmentioning
confidence: 99%